Trends and Methodology of Statistical Research into Consumption Expenditures - Molienė, Ona (Ekonomika, 2000)
Differentiation and concentration analysis of a consumption expenditures level was performed according to Pareto-Lorenz-Gini methodology and referring to the data of separate quarters from the household budget surveys (HBS) conducted from 1997 to 1999. Having performed a secondary grouping according to regressive and progressive levels of consumption expenditures, the dynamics of an average consumption expenditures level were estimated on the basis of an index method; the components of the given time series were defined, and point forecast of a consumption expenditures level was completed considering both factual and deseasonalised data; the strength of the relation between the time series of a consumption expenditures level and the part of food expenditure was estimated. The article also presents conclusions and proposals.